Comparison of short-term clinical outcomes of proximal versus nonproximal lesion location in patients treated with primary percutaneous coronary intervention for ST-elevation myocardial infarction: The PROXIMITI study - Noaman, S.; Goh, C.; Vogrin, S.; Brennan, Angela; Andrianopoulos, N.; Dinh, D.; Lefkovits, J.; Reid, C.; Walton, A.; Al-Mukhtar, O.; Biswas, S.; Stub, D.; et al. (2018)
© 2018 Wiley Periodicals, Inc. Objectives: The objective of this study was to investigate the association of proximal and nonproximal location of culprit coronary lesions with clinical outcomes of patients presenting with ST-elevation myocardial infarction (STEMI) treated by primary percutaneous coronary intervention (PCI). Background: Proximal culprit lesion location in patients presenting with STEMI is associated with increased mortality when compared to distal culprit lesions in the thrombolytic era. The impact of lesion location on clinical outcomes in the era of PCI remains unclear. Methods: We analyzed 3,283 patients with STEMI who enrolled in the Victorian Cardiac Outcomes Registry. We compared outcomes in those with proximal lesion location versus patients with nonproximal location. Results: Of 3,283 participants, 1,376 (41.9%) had a proximal lesion location. Patients with proximal lesion location presented with greater rates of cardiogenic shock and out-of-hospital cardiac arrest, and left ventricular systolic dysfunction, all P<.01. Procedural success rates were similar (96% vs. 95%, P=.08). Patients with proximal lesion location had higher rates of in-hospital and 30-day mortality, major adverse cardiac events (MACE; mortality, myocardial infarction, stent thrombosis, and unplanned revascularization) and major adverse cardiac and cerebrovascular events (MACCE; MACE, and stroke) compared to the nonproximal group, all P<.001. However, on multivariable regression analysis, proximal lesion location was not independently associated with MACE during in-hospital stay or at 30-days (OR 1.32, 95% CI 0.95-1.83, P=.09 and OR 1.23, 95% CI 0.92-1.65, P=.15) respectively. Conclusions: Patients with proximal lesion location had greater hemodynamic instability and higher-risk features; however, proximal lesions per se were not independently associated with worse clinical outcomes compared to nonproximal lesions.